Deciphering the code: the pivotal role of lncRNAs in advancing TNBC therapy - Chen, Weiping; Pan, Zhiyong; Feng, Zhengfu; Wang, Xin; Zhu, Song (Frontiers in Oncology, 2024)
Triple-negative breast cancer (TNBC) represents the most formidable subtype of breast cancer, characterized by a notable dearth in targeted therapeutic options.Deciphering the underlying molecular mechanisms of TNBC is pivotal for improving patient outcomes. Recent scientific advancements have spotlighted long non-coding RNAs (lncRNAs) as key players in the genesis, progression, and metastasis of cancers. This review delineates the significant influence of lncRNAs on the advancement, detection, and neoadjuvant chemotherapy efficacy in TNBC, detailing the diverse expression patterns of aberrant lncRNAs. The paper explores the specific mechanisms by which lncRNAs regulate gene expression in both the nucleus and cytoplasm, with a special focus on their involvement in TNBC's post-transcriptional landscape.Thorough investigations into TNBC-associated lncRNAs not only forge new avenues for early diagnosis and potent treatment strategies but also highlight these molecules as promising therapeutic targets, heralding an era of personalized and precision medicine in TNBC management.